2011
DOI: 10.1103/physrevlett.106.216102
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Resolution at Ionic Crystal Surfaces Using Dynamic Atomic Force Microscopy with Metallic Tips

Abstract: We demonstrate that well prepared and characterized Cr tips can provide atomic resolution on the bulk NaCl(001) surface with dynamic atomic force microscopy in the noncontact regime at relatively large tip-sample separations. At these conditions, the surface chemical structure can be resolved yet tipsurface instabilities are absent. Our calculations demonstrate that chemical identification is unambiguous, because the interaction is always largest above the anions. This conclusion is generally valid for other p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
68
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 21 publications
8
68
0
Order By: Relevance
“…A similar model describes the interaction with charged adatoms on thin insulating layers [7,8]. Moreover, it was found that clean metallic tips carry an intrinsic dipole moment [9,10], which is caused by the Smoluchowski effect [11]. All of these examples underline the importance of atomic-scale electrostatic interactions in NC-AFM.…”
mentioning
confidence: 82%
“…A similar model describes the interaction with charged adatoms on thin insulating layers [7,8]. Moreover, it was found that clean metallic tips carry an intrinsic dipole moment [9,10], which is caused by the Smoluchowski effect [11]. All of these examples underline the importance of atomic-scale electrostatic interactions in NC-AFM.…”
mentioning
confidence: 82%
“…Localized charges of the sample stem from the ions and the vacancy. The localized charges at the tip, in particular, a tip dipole, arise from the tip shape because of the Smoluchowski effect [29,43] and, additionally, from the tip functionalization. Moreover, also image charges have to be taken into account.…”
Section: Theory and Discussionmentioning
confidence: 99%
“…A direct way to identify the lattice sites experimentally, without a priori knowledge of the tip termination and its imaging contrast, is the application of markers with known adsorption sites [29]. We used Cl vacancies in the top layer of NaCl(100), which have previously been studied using scanning tunneling microscopy (STM) by Repp et al [30], to provide unambiguous lattice site identification.…”
Section: Introductionmentioning
confidence: 99%
“…15 Force spectroscopy (FS) experiments, in which tip-sample forces are determined as a function of distance for specific surface sites 16 or over a two-dimensional (2D) area (3D mapping), 17 impose an even stronger constrain on the tip structure and the nature of the interactions. FS has been used to discriminate between the two ionic sublattices on several insulator surfaces, [18][19][20][21][22] to achieve single-atom chemical identification on semiconductors, 23 and to understand the nc-AFM contrast on carbon nanostructures. 24,25 In this work we combine site-specific force measurements and extensive first-principles calculations on TiO 2 (110)-1 × 1, aiming to clarify the origin of the observed nc-AFM contrast and to characterize the tip structures responsible for the protrusion and hole imaging modes.…”
Section: Introductionmentioning
confidence: 99%